BLENDED LEARNING METHOD ASSISTED BY GOOGLE FOR EDUCATION AND PhET INTERACTIVE SIMULATION TO TRAIN SCIENCE PROCESS SKILLS FOR JUNIOR HIGH SCHOOL STUDENTS - Abdul Ghofur; Mohamad Nur; Wasis Wasis (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2022)
The research, which was conducted in Jombang while still adhering to the health protocol, aims to produce high- quality learning tools using the blended learning method assisted by Google for education and PhET interactive simulation to train science process skills in terms of validity, practicality, and effectiveness. The research was carried out in two stages by adapting the 4D model from Thiagarajan followed by the implementation of learning with One Group Pretest-Posttest Design. The results obtained include the validity of the device of 3.68 with a very valid category, practicality in terms of the implementation of learning is very good with an assessment of 3.8. As for the effectiveness in terms of science process skills, students are in the high category with an N-Gain of 0.77 with an average science process skill of 83.33. In practicing science process skills, students still need to deepen in determining variables and defining variables. In addition to an increase in the aspect of science process skills, there is an increase in the cognitive assessment aspect of the product at an N-Gain of 0.78 with an average of 81.67. The obstacle to the application of the blended learning model is that students have not received full permission to operate the device, so there is a need for alternatives to reduce these obstacles. Based on the results of the data analysis, it is concluded that the blended learning device developed is able to train students' science process skills, but requires adjustments to the situation and conditions of students and education units.